2004
DOI: 10.4049/jimmunol.172.11.6858
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Ghosts Are an Efficient Delivery System for DNA Vaccines

Abstract: Mass implementation of DNA vaccines is hindered by the requirement of high plasmid dosages and poor immunogenicity. We evaluated the capacity of Mannheimia haemolytica ghosts as delivery system for DNA vaccines. In vitro studies showed that bacterial ghosts loaded with a plasmid carrying the green fluorescent protein-encoding gene (pEGFP-N1) are efficiently taken up by APC, thereby leading to high transfection rates (52–60%). Vaccination studies demonstrated that ghost-mediated delivery by intradermal or i.m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 23 publications
(20 reference statements)
1
65
0
Order By: Relevance
“…Beta-galactosidase-specific immune response was detected after intravenous immunization of mice with autologous dendritic cells (DCs) transfected ex vivo with pCMVbeta-loaded BGs. 32 An increase of IFN-gamma producing AG-specific CD8 + T cells was observed in animals vaccinated with DNA loaded BGs in response to restimulation by APCs pulsed with peptide containing the immunodominant MHC class I epitope. BGs enhanced expression of MHC class I molecules and costimulatory molecules on DCs.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Beta-galactosidase-specific immune response was detected after intravenous immunization of mice with autologous dendritic cells (DCs) transfected ex vivo with pCMVbeta-loaded BGs. 32 An increase of IFN-gamma producing AG-specific CD8 + T cells was observed in animals vaccinated with DNA loaded BGs in response to restimulation by APCs pulsed with peptide containing the immunodominant MHC class I epitope. BGs enhanced expression of MHC class I molecules and costimulatory molecules on DCs.…”
mentioning
confidence: 97%
“…The use of BGs as candidate vaccines and advanced drug carriers can be found in several recent reviews. 24,27,29,[32][33][34][35][36] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that the Th2 (humoral) immune response against the DNA encoded antigen was stronger than the Th1 (cellular) response, which is rather unusual for DNA vaccines, and can most likely be attributed to the delivery and BG induced signaling. 77 A more sophisticated and recently developed version of loading BG with DNA uses the specific interaction of an inner membrane anchored DNA binding protein with the corresponding operator region on target plasmid. This allows a one step DNA loading and BG formation process.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%